Proteasome, a Promising Therapeutic Target for Multiple Diseases Beyond Cancer - Cao Y; Zhu H; He R; Kong L; Shao J; Zhuang R; Xi J; Zhang J (Dove Medical Press, 2020)
Yu Cao,1,* Huajian Zhu,1,* Ruoyu He,2 Limin Kong,3 Jiaan Shao,1 Rangxiao Zhuang,2 Jianjun Xi,2 Jiankang Zhang1 1School of Medicine, Zhejiang University City College, Hangzhou, Zhejiang Province, 310015, People’s Republic of China; 2Department of Pharmaceutical Preparation, Hangzhou Xixi Hospital, Hangzhou, Zhejiang Province, 310023 People’s Republic of China; 3Department of Pharmacy, The First Affiliated Hospital, Zhejiang University, Hangzhou, Zhejiang Province, 310003, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jianjun XiDepartment of Pharmaceutical Preparation, Hangzhou Xixi Hospital, Hangzhou, Zhejiang Province 310023, People’s Republic of ChinaEmail xjianjun@foxmail.comJiankang ZhangSchool of Medicine, Zhejiang University City College, Hangzhou, Zhejiang Province 310015, People’s Republic of ChinaEmail zjk0125@yeah.netAbstract : Proteasome is vital for intracellular protein homeostasis as it eliminates misfolded and damaged protein. Inhibition of proteasome has been validated as a powerful strategy for anti-cancer therapy, and several drugs have been approved for treatment of multiple myeloma. Recent studies indicate that proteasome has potent therapeutic effects on a variety of diseases besides cancer, including parasite infectious diseases, bacterial/fungal infections diseases, neurodegenerative diseases and autoimmune diseases. In this review, recent developments of proteasome inhibitors for various diseases and related structure activity relationships are going to be summarized.Keywords: proteasome inhibitor, infectious diseases, autoimmune diseases, neurodegenerative diseases, drugs